Implementation of Posyandu Program in Fulfilling the Rights of Pregnant Women and Toddlers in Cibinong Sub-District, Bogor District, a Case Study in Pondok Rajeg Village - Maruapey, Muhammad Husein; Danil, Mahmud; Murni, Endang Sri; Ramadhan, Rahmasari; Pratama, M. Rifa’i Eka (MultiTech Publisher, 2024)
Health issues are fundamental in society. Moreover, after COVID-19, several adjustments were made to strengthen public health. Then the importance of developing quality human resources as a national priority cannot be separated from good nutritional status, especially in nutritionally vulnerable groups such as pregnant women and toddlers. Optimal nutritional conditions for pregnant women are very important because they have the potential to influence the growth and development process of the fetus. Malnutrition in pregnant women can increase the risk of giving birth to babies with low birth weight (LBW) and stunting. Likewise, toddlers as a group who are in a period of rapid growth and development are very vulnerable to malnutrition. Therefore, special attention to pregnant women and toddlers needs to be increased in an effort to improve national nutritional status. This research was conducted to determine the success of the implementation of the Posyandu program in Pondok Rajeg Village, Cibinong District, Bogor Regency in an effort to fulfill the rights of pregnant women and toddlers. The method used is a descriptive qualitative method using George C. Edward III's theory with four dimensions, namely Communication, Resources, Disposition and Bureaucratic Structure. The success of the implementation or implementation of the Posyandu program in Pondokrajeg Village, Cibinong District, Bogor Regency has been good, which can be seen from the results of research with resource persons, supporting documents and reports on improving the health of pregnant women and toddlers in Pondok Rajeg District, Cibinong District, Bogor Regency